High expression of ANRIL correlated with the poor prognosis in patients with cancer: A meta-analysis. Issue 36 (9th September 2022) - Liu, Yun; Zhu, Linqi; Zhao, Wenjun; Zhou, Yong; Shao, Shihe
Abstract : Background: ANRIL, also called CDKN2B antisense RNA 1, is an important genetic susceptibility locus for cardiovascular diseases and associated with numerous pathologies, including several human cancers. Objective: The relationship between ANRIL and the clinical outcome or prognosis of cancer patients was analyzed in this meta-analysis. Methods: One thousand seven hundred eight cancer patients were selected in 23 studies from 3 databases (Pubmed, Cochrane Library, and EMBASE). Results: A fixed-effects model indicated that the high expression of ANRIL is obviously linked to poor overall survival (OS) (Hazard ratio [HR] = 1.77, 95% confidence interval [CI] = 1.57–2.00, P < .00001); the random-effects model revealed poor disease-free survival (DFS) (HR = 1.86, 95% CI: 1.46–2.37, P < .00001). A high level of ANRIL expression was also associated with the tumor size (small vs large, odds ratio [OR] = 0.57, 95% CI: 0.39–0.83, P = .003), TNM stage (I + II vs III + IV; OR = 0.40, 95% CI: 0.24–0.69, P = .0008), and lymph node metastasis (LNM) (Yes vs No, OR = 3.66, 95% CI: 1.46–9.17, P = .006). ANRIL was not related significantly to histologic differentiation compared to poor with moderate + well; the OR value is 0.74, 95% CI: 0.26–2.12, P = .58. In addition, evidence suggested that a high level of ANRIL was positively associated with human cancer type, follow-up time, and sample size. Conclusion: This meta-analysis demonstrated that ANRIL may be a valuable biomarker for predicting poor prognosis in cancer patients.